'Just because you like it doesn't mean I will too:' Cross‐cultural similarities in ignoring others' opinions. Issue 3 (11th February 2015) - Lee, Minha; Wilson, Timothy D.; Eggleston, Casey M.; Gilbert, Daniel T.; Ku, Xyle
<x xml:space="preserve">Abstract</x> Members of East Asian cultures are more likely to conform in public settings than are members of Western cultures. Little research has examined, however, whether East Asians are more likely to privately accept the views held by others. In two studies we gave European American and Korean participants descriptions of unusual food combinations, information about how much one peer had liked the food combinations, or both kinds of information, and asked them to predict how much they would like the foods. When people knew only how another person felt (without a description of the food combinations), both Koreans and Americans based their predictions on the other person's ratings. When people received descriptions of the foods and the ratings of another person, however, both Koreans and Americans based their predictions more on the descriptions than on how the other person felt. In short, we found no cultural differences in the extent to which people use another person's opinion to inform their own opinions.